Shoeprints on Shoe covers Obtained Using Special Thermal Devices as Objects of Traceological Forensic Examination - I. V. Latyshov (Теория и практика судебной экспертизы)
The article deals with the issues of traceological forensic examination of shoeprints generated while putting shoe covers upon shoes using special thermal devices, and during subsequent walking in shoes. A sole surface shoeprint appears on the shoe as a result of transfer of dust, oil and other substances’ layering on the shoe sole from road surfacing. The peculiarity of the formation mechanism of these traces points to the heating of the polyvinyl chloride film of the shoe cover at the time of the shoeprint formation on the shoe cover, as well as to the fact of wearing shoes with shoe covers on. While wearing shoes, after the shoeprint formation on the shoe covers, the sole of the shoes repeatedly contacts with the shoe covers and, accordingly, with the shoeprints already being on them. The contact frequency is determined by the time of walking and the number of steps taken while wearing the shoes. It is noted that the repeated contact interaction of the shoe sole and the surface shoeprint on the shoe cover leads to chafing and trampling of the shoeprint and to deterioration of its quality. This results in reducing the sharpness (blurring) of the outline elements of the shoeprint pattern, changing their contour shape and fading of most of the sole surface microrelief features in the shoeprints. When solving the issue of identity of the shoe which formed the shoeprint in the shoe cover, it is proposed to pay special attention to the signs of the shoe sole wear, visualized in the shoeprints in the form of scuff zones. They are exactly the ones selectable for distinction of the final shoeprint pattern blurred by the multiple contact of the sole with the shoe cover. To increase the effectiveness of comparing shoeprints on the shoe covers with experimental shoeprints, it is recommended to use the technique of constructing templates – the geometric patterns taking into account the signs of localization, shape, size of wear zones, and the relative location display of these zones in the shoeprint.